THE ELEMENTS OF THE BASIC PHOTOMETRICAL CIRCLES ON THE SURFACE OF THE SPHERICAL PLANET AND DETERMINATION OF THEIR PLANETOCENTRIC POSITIONS - Mikhalchuk, V. V. (Одеські астрономічні публікації, 2016)
Formulae for determination of planetocentric positions of the basic photometrical circles on the surface of the spherical planet (the equator of intensity, an orthographic limb and orthographic terminator) from the elements of these circles specified to conditions of illumination of its visible disk are obtained. The planetocentric positions of the basic photometrical circles on visible disks of terrestrial planets from their physical ephemerides are calculated.